Sosialisasi Technopreneurship Produktif Dan Kreatif Pada Masyarakat Masbagik Utara Baru - Dedy Febry Rachman; Syaiful Amri (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi AMM, 2026)
The development of information and communication technology in the digital era presents both opportunities and significant challenges for village-level economies. Masbagik Utara Baru Village in East Lombok Regency possesses promising potential for local Micro, Small, and Medium Enterprises (MSMEs); however, the utilisation of digital technology for operational development and business marketing remains relatively limited. This community service initiative—conducted through a session on